Prediksi Kesesuaian Lahan Untuk Tanaman Jagung Menggunakan Sistem Informasi Geografis (SIG) Di Kabupaten Bone Bolango Provinsi Gorontalo - Alisya Kabanya; Nurfaika Nurfaika; Rakhmat Jaya Lahay (-, 2026)
Corn (Zea mays L.) is one of the strategic agricultural commodities in Indonesia. This study aims to predict the level of land suitability for corn cultivation using Geographic Information System (GIS) Technology in Bone Bolango Regency. A quantitative descriptive method was used through a spatial analysis approach in the form of overlay on five biophysical parameters: slope, elevation, precipitation, soil type, and land cover. The results of the analysis show that land suitability is divided into five classes. The Absolutely Unsuitable (N2) class dominates the study area covering 108,923 ha (58.23%), followed by the Unsuitable (N1) class covering 41,412 ha (22.13%) due to the limiting factors of steep slopes, high elevations, and forest areas. Meanwhile, potential areas include the Very Suitable (S1) class covering 13,433 ha (7.19%), Suitable (S2) class covering 10,065 ha (5.38%), and Marginally Suitable (S3) class covering 13,227 ha (7.07%). In conclusion, the effective use of GIS produces accurate spatial information to support corn agricultural development planning.